PLATINUM CATALYTIC EFFECT ON OXYGEN FUGACITY OF CO2-H2 GAS MIXTURES MEASURED WITH ZRO2 OXYGEN SENSOR AT 105 PA FROM 1300 TO 700OC - Miyamoto M.; Mikouchi T. (My University, 1996)
The oxygen fugacity of CO2-H2 gas mixtures were measured with a ZrO2 oxygen sensor at high temperatures in a furnace. We confirmed that the oxygen fugacity values measured by the ZrO2 cell are more reducing than those of the CO2-H2 gas mixtures calculated by using JANAF data at temperatures below 1150oC as was previously reported by Huebner (1975). We successfully decreased the deviation of the measured oxygen-fugacity value from the calculated one down to temperature of 800oC by using a Pt catalyst. Our results suggest that the deviation is probably due to incomplete equilibration of the gases.